Peranan dan Peningkatan PPATK Dalam Mendukung Upaya Pencegahan Pencucian Uang Oleh Pejabat Di Indonesia (Studi Kasus Rafael Alun) - Al Fath (Fakultas Hukum Universitas Pembangunan Nasional Veteran Jakarta, 2023)
Money laundering is an illegal act that has a negative impact on the economy and financial stability of a country. In Indonesia, PPATK (Financial Transaction Reports and Analysis Center) has an important role in the prevention and handling of money laundering crimes. In facing the times and technology, PPATK needs to increase the use of information technology to improve the quality of its work. This article examines the role of PPATK in the case of Rafael Alun, a tax official who was involved in money laundering. PPATK plays a role in identifying and recovering assets originating from these crimes. PPATK also conducts training and outreach, analyzes financial transactions, reports suspicious transactions, and cooperates with law enforcement agencies in prevention and prevention efforts. In addition, this article discusses the importance of developing information technology in improving the quality of PPATK. Increasing sophisticated data analysis systems and using artificial intelligence (AI) technology can assist PPATK in identifying suspicious transactions quickly and accurately. However, the use of this technology must be carried out ethically and maintain user privacy. In addition, the application of biometric identification as a method of strengthening customers can strengthen the process of preventing money laundering. In conclusion, this article emphasizes the importance of using information technology in preventing money laundering by PPATK. By utilizing the right technology, PPATK can be more effective in fighting money laundering and maintaining state financial stability.